2007
DOI: 10.1271/bbb.70240
|View full text |Cite
|
Sign up to set email alerts
|

Plant-TypeN-Glycans Containing Fucose and Xylose in Bryophyta (Mosses) and Tracheophyta (Ferns)

Abstract: The presence of typical plant-type N-glycans (eg, M3FX, Gn2M3FX, and Le a 2M3FX) in mosses, ferns, and other organisms was examined to determine which plant initially acquired glycosyltransferases to produce plant-type N-glycans during organic evolution. No M3FX-type N-glycan was detected in lichens (Cladonia humilis) or in any one of the three preland plants Enteromorpha prolifera, Ulva pertusa Kjellman, and Chara braunii Gmelin. In Bryophyta, M3FX-type Nglycan was detected at trace amounts in Anthocerotopsid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 22 publications
(39 reference statements)
0
12
0
Order By: Relevance
“…However, building blocks specific to or preferred by some kingdoms, phyla or classes for N ‐glycoprotein production are known, e.g. the frequent usage of β‐D‐xylose (Xyl) in plants (Mega, ), gastropods (Gutternigg et al ., ; Velkova et al ., ) and trematodes (Khoo et al ., ; Hokke et al ., ) and N ‐glycolyl‐α‐D‐neuraminic acid (NeuGc) in non‐human mammals as well as specific glycosidic linkages e.g. α1,3‐linked ‘core’ fucosylation preferred by plants and invertebrates (Rini & Esko, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, building blocks specific to or preferred by some kingdoms, phyla or classes for N ‐glycoprotein production are known, e.g. the frequent usage of β‐D‐xylose (Xyl) in plants (Mega, ), gastropods (Gutternigg et al ., ; Velkova et al ., ) and trematodes (Khoo et al ., ; Hokke et al ., ) and N ‐glycolyl‐α‐D‐neuraminic acid (NeuGc) in non‐human mammals as well as specific glycosidic linkages e.g. α1,3‐linked ‘core’ fucosylation preferred by plants and invertebrates (Rini & Esko, ).…”
Section: Introductionmentioning
confidence: 99%
“…GNBs from plant polysaccharides are little known, and LNB is known to exist in biosynthetic intermediates of N-linked glycoproteins during the processing of plant N-glycans in the Golgi apparatus, which is quite a minor component in plants (39). Moreover, there are no endo-␣-N-acetylgalactosaminidase (7,40,41) and lacto-N-biosidase (5) (GNB-and LNB-releasing enzyme, respectively) homologs in the genome of C. phytofermentans.…”
mentioning
confidence: 99%
“…MathieuRivet et al (2013) showed that the N-glycan structures in Chlamydomonas reinhardtii, a green unicellular alga, are almost all highmannose type and its xylosylated forms [13], and Mega (2007) has proposed that the appearance of paucimannose type N-glycans was one of the major events in plant evolution [14]. In addition, Ulvskov et al (2013) have proposed that the numbers of glycosyltransferases reflect the process of adaptation in plant evolution [15].…”
Section: Biological Significance Of Transitions In N-glycan Structurementioning
confidence: 99%
“…On the basis of our own work and a series of recent studies, we propose the hypothesis that N-glycan evolution proceeded simultaneously with plant evolution. Thus, the first evolutionarily significant event was the appearance of paucimannose type N-glycans in Bryophyta [14]. These plants developed glycosyltransferases and glycosylhydrolases to convert high-mannose type N-glycan into paucimannose type N-glycan.…”
Section: Biological Significance Of Transitions In N-glycan Structurementioning
confidence: 99%